Fetal ovarian cyst with prenatal torsion of the pedicle diagnosed in the third trimester: A case report - Hayase Nitta; Tadatsugu Kinjo; Yoshino Kinjyo; Hisako Yamada; Hitoshi Masamoto; Yoichi Aoki (Elsevier, 2022)
Ovarian cysts develop rarely in fetuses during pregnancy and usually disappear after birth. However, during pregnancy, torsion and rupture of the cyst can occur and it is necessary to manage such cases. At present, there is no standardized prenatal or neonatal treatment. However, the preservation of ovarian function is an important consideration. Here, we present a case involving a 35-year-old woman who gave birth to an infant with a complicated ovarian cyst, which was resolved through laparoscopic surgery on the third day after birth. The prenatal diagnosis of the fetal ovarian cyst was performed prenatally using ultrasound and magnetic resonance imaging (MRI). However, torsion of the ovarian pedicle was suspected because of dorsal thickening of the cyst wall and fluid formation indicated by high intensity on T1- and T2-weighted MRI. Surgery was complicated due to involvement in the torqued pedicle of the left fallopian tubal fimbria, which was released. The cyst was drained and partially resected, and then the pedicle torsion was released. By four years and five months of follow-up, there had been no ovarian cyst findings on ultrasound or MRI. Larger cysts are more likely to involve torsion of the ovarian pedicle and potential bleeding. Considering that, in this case, the cyst was large and proved to be ischemic-hemorrhagic, the decision to operate seemed justified.